Oil-resistant, anti-skid and anti-static rubber material and preparation method and use thereof

Through the specific rubber material composition ratio and process processing, the existing rubber soles are easily expanded and slipped in oily environments, and the comprehensive performance of oil resistance, anti-slip and anti-static is improved, and the service life is extended.

CN116199949BActive Publication Date: 2025-04-11FUJIAN PUTIAN LIANSHENG FOOTWEAR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211697407.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-04-11
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The existing rubber soles are prone to expand and slip in oily environments, and lack anti-static effects, which pose safety hazards and short service life.

Method used

Through specific composition ratios, a rubber material that is resistant to oil, anti-slip and anti-static is prepared, including butadiene rubber, nitrile rubber 220s and nitrile rubber 7030, combined with ultrafine white smoke and anti-static agent, is treated using refining and vulcanization processes.

Benefits of technology

The oil resistance of rubber materials is achieved with an expansion rate of less than 6%, the anti-slip performance of heavy oil is as high as 0.45, and the anti-static effect is as low as 5 ohm resistance value, which significantly improves the material's adaptability and service life in an oily environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005277066360000011
    Figure FDA0005277066360000011
  • Figure FDA0005277066360000012
    Figure FDA0005277066360000012
  • Figure FDA0005277066360000021
    Figure FDA0005277066360000021
Patent Text Reader

Abstract

The present application discloses an oil-resistant, anti-slip and anti-static rubber material, which comprises the following components: 5-10 parts by weight of butadiene rubber, 20-25 parts by weight of nitrile rubber 220s, 18-20 parts by weight of nitrile rubber 7030, 10-14 parts by weight of ultrafine (gas phase) white smoke, 6-6.5 parts by weight of antistatic agent, 0.7-0.75 parts by weight of accelerator DM, 1.6-1.7 parts by weight of antioxidant OH3, 3.5 4 parts by weight of zinc carbonate, 0.4-0.5 parts by weight of stearic acid, 1.2-1.5 parts by weight of polyethylene glycol PEG-400, 1.5-1.6 parts by weight of wear-resistant oil and 1.2-1.4 parts by weight of insoluble sulfur as a vulcanizing agent, wherein the weight ratio of nitrile rubber 220s to nitrile rubber 7030 is between 1.03-1.35, and the weight ratio of cis-1,4-butadiene rubber to nitrile rubber 220s is between 0.28-0.38. The rubber material obtained by the present invention retains the physical properties of general rubber soles, and the oil resistance even reaches an expansion rate of less than 5%, the heavy oil anti-slip is as high as 0.45, and the antistatic effect is as low as less than 5 ohm resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of rubber materials, and in particular to an oil-resistant, anti-skid and anti-static rubber material particularly suitable for shoemaking and a preparation method thereof. Background Art

[0002] As the application technology of rubber materials in sole manufacturing continues to mature, the current general rubber sole technology products have extremely poor adaptability in oily application environments. They will absorb oil and expand rapidly, causing the shoes to be scrapped. In addition, the anti-slip performance is very poor in heavy oil environments, posing serious safety hazards.

[0003] The general oil resistance of rubber soles on the market is 50% expansion rate (the higher the worse), heavy oil anti-slip 0.1 (the higher the better), and no anti-static effect (the higher the ohm value, the worse the effect). Brand products that focus on the research and development of labor protection fields have corresponding oil-resistant special shoes. This type of product has an oil resistance of 12% expansion rate, heavy oil anti-slip 0.3, and an anti-static effect of 10 ohms. Therefore, people have been committed to researching and developing an oil-resistant, anti-slip and anti-static rubber material, which is also particularly suitable for making soles. Summary of the invention

[0004] One purpose of the present invention is to solve the technical problem that labor protection shoes are prone to swelling and slipping when performing special operations in an oily environment. The present invention breaks through the upper limit of the oil resistance and heavy oil anti-slip performance of rubber soles without affecting other physical properties. Another purpose of the present invention is that in addition to considering the situation of oily surface operations, the present invention also has excellent antistatic effect.

[0005] To this end, the present application provides an oil-resistant, anti-slip and anti-static rubber material, which comprises the following components:

[0006]

[0007]

[0008] The weight ratio of nitrile rubber 220s to nitrile rubber 7030 is between 1.03-1.35, and the weight ratio of butadiene rubber to nitrile rubber 220s is between 0.28-0.38.

[0009] In addition, the present application also provides a method for preparing an oil-resistant, anti-slip and anti-static rubber material, the method comprising the following steps:

[0010] 1) Put cis-1,4-butadiene rubber, nitrile rubber 220s and nitrile rubber 7030 into an internal mixer and plasticate for 90-100 seconds at a machine temperature of 90-100°C;

[0011] 2) Then pour in small medicine and one third of superfine white smoke, and plasticize for 60-70 seconds at a temperature of 100-110°C, wherein the small medicine refers to other ingredients in the formula except butadiene rubber, nitrile rubber 220s, nitrile rubber 7030, superfine white smoke and insoluble sulfur as a vulcanizing agent;

[0012] 3) Then pour in one third of white smoke and masticate for 60-70 seconds at a temperature of 110-115°C;

[0013] 4) Pour in the remaining white smoke and plasticize for 60-70 seconds at a temperature of 120-125°C;

[0014] 5) Lift the hammer to clean, put down the hammer to plasticize, repeat at least three times, time 120-130 seconds, temperature 130-135℃;

[0015] 6) Pour the plasticized rubber into the turbine and continue plasticizing for at least 180 seconds, then roll it up to produce a sheet;

[0016] 7) Add vulcanizing agent to the stored rubber material in an open mixing mill, mix evenly, and roll up to produce sheets.

[0017] 8) The temperature of the rubber vulcanizer is 160±10℃ and the pressure is 155±5KG / CM2 for vulcanization.

[0018] The oil resistance of the rubber material obtained by the present invention reaches an expansion rate of less than 6%, and even reaches an expansion rate of less than 5%, and the heavy oil anti-skid performance is as high as 0.45, and the antistatic effect is as low as less than 5 ohm resistance. The rubber material obtained by the present invention has better oil resistance, heavy oil anti-skid performance and antistatic effect than professional oil-resistant labor shoes on the market, which will make up for the shortcomings of products on the market in application in more severe oily environments, and has a longer service life. DETAILED DESCRIPTION

[0019] Cis-1,4-butadiene rubber is a synthetic rubber with a regular structure formed by the polymerization of butadiene, and its cis-structure content is more than 95%. Cis-1,4-butadiene rubber is the second largest synthetic rubber after styrene-butadiene rubber. Compared with natural rubber and styrene-butadiene rubber, cis-1,4-butadiene rubber has excellent cold resistance, wear resistance and elasticity after vulcanization. As an example, cis-1,4-butadiene rubber BR1208 is used in the present invention, and for example, cis-1,4-butadiene rubber BR1208 supplied by Yanshan Petrochemical is used in the embodiment.

[0020] Nitrile rubber (NBR) is a copolymer formed by polymerization of acrylonitrile and butadiene monomers, mainly produced by low-temperature emulsion polymerization, with excellent oil resistance, high wear resistance, good heat resistance and strong adhesion. Its disadvantages are poor low temperature resistance, poor ozone resistance, poor insulation performance and slightly low elasticity. The present application obtains better oil resistance and anti-slip properties by selecting specific combinations between different types of nitrile rubbers.

[0021] Nitrile rubber 220s has good oil resistance and good air tightness, second only to butyl rubber. Compared with other butyl rubbers, it has a higher acrylonitrile content, better wear resistance and oil resistance, and is a semiconductor rubber. Nitrile rubber 220s is widely used in the manufacture of gaskets, sealing gaskets, oil seals for fuel pipe transportation, Freon delivery pipes, and printing rubber rollers.

[0022] NBR 7030 is a blend of 70% medium to high acrylonitrile content NBR mixed with 30% polyvinyl chloride resin. Since NBR 7030 has been pre-polymerized, the rubber can be mixed at room temperature and employed in subsequent plant operations. NBR 7030 has sufficient stabilizers for normal aging conditions and can be handled with normal mixing procedures. It has high composite strength, relatively good physical properties and excellent extrusion processing properties, providing a smooth surface for the surface of the product.

[0023] The applicant has found that by mixing the two nitrile rubbers, ie, nitrile rubber 220s and nitrile rubber 7030, in a specific ratio, the wear resistance and oil resistance of the nitrile rubber 220s can be further improved, and the anti-slip property of the nitrile rubber 7030 can be further improved.

[0024] The antistatic agent used in the present application has no special requirements. Generally, the antistatic agent that can be used for antistatic soles can be used. Preferably, the antistatic agent used has good compatibility with the rubber used in the present application, does not affect the physical property of rubber products, and the antistatic effect can be maintained for a long time. The inventor found in the research and development process that in order to allow the antistatic agent to be compatible with rubber evenly, the amount of the antistatic agent can not be too large, and the weight ratio of itself and nitrile rubber 220s is between 0.25-0.33, preferably between 0.25-0.3.

[0025] In the present application, ultrafine (fumed) white smoke is a type of silicon dioxide.

[0026] In the present application, each small medicine is a reagent commonly used in the field of shoemaking, and there is no particular limitation. However, from the performance obtained by the present invention, the composition and dosage of these small medicines together constitute the overall scheme of the present invention. The applicant boldly believes that if these small materials are not used in combination, the rubber product obtained by the present application may not be able to achieve such a good industry performance breakthrough.

[0027] In a particularly specific embodiment, the present application also provides a method for preparing an oil-resistant, anti-slip and anti-static rubber material, the method comprising the following steps:

[0028] 1) Put 1,2-butadiene rubber BR1208, nitrile rubber 220s and nitrile rubber 7030 into an internal mixer and plasticate for 90-100 seconds at a machine temperature of 90-100°C;

[0029] 2) Lift the heavy hammer and pour in the small medicine and one-third of superfine white smoke, and plasticize for 60-70 seconds at a temperature of 100-110℃;

[0030] 3) Lift the heavy hammer to clean, then pour in one third of white smoke, plasticize for 60-70 seconds, the temperature is 110-115℃;

[0031] 4) Lift the heavy hammer to clean, pour in the remaining white smoke, and plasticize for 60-70 seconds at a temperature of 120-125°C;

[0032] 5) Lift the hammer to clean, put down the hammer to plasticize, repeat at least three times, time 120-130 seconds, temperature 130-135℃;

[0033] 6) Pour the plasticized rubber into the turbine, continue plasticizing for 180 seconds, roll up the sheet, hang it on a rack to dry, let it cool, then weigh it, pack it in a PE bag, and store it for 24 hours for use;

[0034] 7) Add vulcanizing agent to the stored rubber in an open mixing mill, mix evenly, and roll up to form sheets; dry for 4 hours and cut the sheets for later use.

[0035] 8) The temperature of the rubber vulcanizer is 160±10℃, the pressure is 155±5KG / CM2, and the vulcanization time is set according to the product quality, for example, 320 seconds.

[0036] In the preparation method of the present invention, considering that the particle size of white smoke is very fine and in order to make the dispersion of white smoke more uniform, a process of dividing it into three equal batches for plasticizing is adopted. This process also promotes the acquisition of the rubber material claimed in the present invention to a certain extent.

[0037] In addition, without being bound by any theory, the inventors believe that the 90-100°C temperature used in the plasticizing process of the nitrile rubber also promotes the plasticizing of the nitrile rubber, making it better compatible with other components.

[0038] The rubber material obtained by the present invention has the physical properties of general rubber soles, and the oil resistance reaches an expansion rate of less than 5%, the heavy oil anti-slip is as high as 0.45, and the antistatic effect is as low as 5 ohms resistance value. The tests of these properties are carried out according to industry standards, and the detailed description of these standards is described in the following embodiments.

[0039] Example

[0040] The present invention is further described below by way of examples, but these examples are only for illustration and the present invention should not be considered to be limited to these examples.

[0041] Table 1. Details of the raw materials used in the examples

[0042] Material Name Product Number Manufacturer or supplier Butadiene rubber BR1208 Yanshan Petrochemical Nitrile rubber 220s Japan JSR Co., Ltd. Nitrile rubber 7030 LG Chem Ultrafine (gas phase) white smoke W216 Xiamen Shengzhiyao Chemical Co., Ltd. Antistatic Agents none Wenzhou Zhaoxu Shoe Materials Co., Ltd. Accelerator DM none Putian Jinzhiyuan Chemical Co., Ltd. (Supplier) Antioxidant OH3-MG Taiwan Xiang Rubber (Shenzhen) Co., Ltd. Zinc Oxide Transparent zinc oxide Taiwan Xiang Rubber (Shenzhen) Co., Ltd. Stearic acid 1838 Fujian Anyuan Rubber Technology Co., Ltd. Polyethylene glycol PEG4000 Liaoning Aoke Chemical Co., Ltd. Wear-resistant oil Si50 Taiwan Xiang Rubber (Shenzhen) Co., Ltd. Vulcanizing agent Insoluble sulfur Putian Yitai Plastic Material Co., Ltd.

[0043] Table 2. Composition of formulas 1 to 3 used in Examples 1-3

[0044] Material Name Formula 1 (parts by weight) Formula 2 (parts by weight) Formula 3 (parts by weight) Butadiene rubber BR1208 6 8 7 Nitrile rubber 220s 20 22 24 Nitrile rubber 7030 19 20 18 Ultrafine (gas phase) white smoke 12 10 13 Antistatic Agents 6 6 6 Accelerator DM 0.7 0.75 0.7 Antioxidant OH3 1.6 1.7 1.65 Zinc carbonate 3.7 3.7 3.7 Stearic acid 0.4 0.4 0.4 Polyethylene glycol PEG-400 1.5 1.4 1.2 Wear-resistant oil 1.5 1.5 1.6 Vulcanizing agent insoluble sulfur 1.2 1.2 1.2

[0045] Table 3. Test standards for technical parameters involved in this application and test results of products

[0046] 1. Oil resistance: ≤6% expansion rate (GB / T 20991-2007 8.6)

[0047] 2. Heavy oil anti-slip ≥ 0.46 (ISO 13287:2012SRC)

[0048] 3. Antistatic performance ≤ 4Ω (GB / T 20991-2007 5.10)

[0049] 4. Hardness: 65±3A (GB / T 3903.4-2008);

[0050] 5. Specific gravity: ≤1.18g / cm 3 (GB / T 533-2008);

[0051] 6. Wear resistance: ≤100mm 3 (GB / T 9867-2008);

[0052] 7. Tensile strength: ≥12Mpa (GB / T 3903.22-2008);

[0053] 8. Elongation: ≥450% (GB / T 3903.22-2008);

[0054] 9. Tear strength: ≥15N / mm (GB / T 3903.22-2008);

[0055] 10. Ozone: ≥ Level 3 (temperature: 40°C; humidity: 65% RH; ozone concentration: 50pphm; 10. Time: 6H)

[0056] Example 1, using formula 1

[0057] 1. Put 6 parts by weight of cis-butadiene rubber BR1208, 20 parts by weight of nitrile rubber 220s, and 19 parts by weight of nitrile rubber 7030 into an internal mixer and plasticate for 90 seconds at a machine temperature of 90°C.

[0058] 2. Lift the heavy hammer and pour in 6 parts by weight of antistatic agent, 0.7 parts by weight of accelerator DM, 1.6 parts by weight of antioxidant OH3, 3.7 parts by weight of zinc carbonate, 0.4 parts by weight of stearic acid, 1.5 parts by weight of polyethylene glycol PEG-400, 1.5 parts by weight of wear-resistant oil and one third of 12 parts by weight of ultrafine (gas phase method) white smoke, and plasticize for 60 seconds at a temperature of 110°C;

[0059] 3. Lift the heavy hammer to clean, then pour in one third of 12 parts by weight of ultrafine (gas phase) white smoke, plasticate for 60 seconds, temperature 115°C;

[0060] 4. Lift the heavy hammer to clean, pour in the remaining one third of 12 parts by weight of ultrafine (gas phase method) white smoke, and plasticize for 60 seconds at a temperature of 125°C;

[0061] 5. Lift the heavy hammer to clean, put down the heavy hammer to plasticize, repeat three times, time 120 seconds, temperature 135℃;

[0062] 6. Pour the plasticized rubber into the turbine and continue plasticizing for 180 seconds, roll it up, hang it on a rack to dry, let it cool, then weigh it, pack it in a PE bag, and store it for 24 hours for use;

[0063] 7. Add 1.2 parts by weight of insoluble sulfur as a vulcanizing agent to the stored rubber in an open mill, mix evenly, and roll up to form sheets; dry for 4 hours and cut the material for later use;

[0064] 8. The temperature of the rubber vulcanizing machine is 160℃, the pressure is 155KG / CM2, the exhaust is three times, and the vulcanization time is 320 seconds.

[0065] The finished product was tested and its performance parameters are shown in the following table:

[0066] Test results:

[0067] Oil resistance %: 6% expansion rate;

[0068] Heavy oil anti-slip: 0.46;

[0069] Antistatic Ω: 4;

[0070] Hardness A: 65;

[0071] Specific gravity g / cm 3 : 1.17;

[0072] Wear resistance mm 3 :95;

[0073] Tensile strength MPa: 14;

[0074] Elongation %: 480;

[0075] Tear strength N / mm: 16;

[0076] Ozone level: 3.

[0077] Ozone test conditions (temperature: 40°C; humidity: 65% RH; ozone concentration: 50 pphm; time: 6 hours)

[0078] Example 2, using formula 2

[0079] 1. Put 8 parts by weight of cis-butadiene rubber BR1208, 22 parts by weight of nitrile rubber 220s, and 20 parts by weight of nitrile rubber 7030 into an internal mixer and plasticate for 90 seconds at a machine temperature of 90°C.

[0080] 2. Lift the heavy hammer and pour in 6 parts by weight of antistatic agent, 0.75 parts by weight of accelerator DM, 1.7 parts by weight of antioxidant OH3, 3.7 parts by weight of zinc carbonate, 0.4 parts by weight of stearic acid, 1.4 parts by weight of polyethylene glycol PEG-400, 1.5 parts by weight of wear-resistant oil and one third of 10 parts by weight of ultrafine (gas phase method) white smoke, and plasticize for 60 seconds at a temperature of 110°C;

[0081] 3. Lift the heavy hammer to clean, then pour in one third of 10 parts by weight of ultrafine (gas phase) white smoke, plasticate for 60 seconds, temperature 115°C;

[0082] 4. Lift the heavy hammer to clean, pour in the remaining one third of 10 parts by weight of ultrafine (gas phase) white smoke, and plasticize for 60 seconds at a temperature of 125°C;

[0083] 5. Lift the heavy hammer to clean, put down the heavy hammer to plasticize, repeat three times, time 120 seconds, temperature 135℃;

[0084] 6. Pour the plasticized rubber into the turbine and continue plasticizing for 180 seconds, roll it up, hang it on a rack to dry, let it cool, then weigh it, pack it in a PE bag, and store it for 24 hours for use;

[0085] 7. Add 1.2 parts by weight of insoluble sulfur as a vulcanizing agent to the stored rubber in an open mill, mix evenly, and roll up to form sheets; dry for 4 hours and cut the material for later use;

[0086] 8. The temperature of the rubber vulcanizing machine is 160℃, the pressure is 155KG / CM2, the exhaust is three times, and the vulcanization time is 320 seconds.

[0087] The finished product was tested and its performance parameters are shown in the following table:

[0088] Test results:

[0089] Oil resistance %: 5% expansion rate;

[0090] Heavy oil anti-slip: 0.49;

[0091] Antistatic Ω: 3;

[0092] Hardness A: 64;

[0093] Specific gravity g / cm 3 : 1.15;

[0094] Wear resistance mm 3 :90;

[0095] Tensile strength MPa: 15;

[0096] Elongation %: 510;

[0097] Tear strength N / mm: 20;

[0098] Ozone level: 3.

[0099] Ozone test conditions (temperature: 40°C; humidity: 65% RH; ozone concentration: 50 pphm; time: 6 hours)

[0100] Example 3, using formula three

[0101] 1. Put 7 parts by weight of cis-butadiene rubber BR1208, 24 parts by weight of nitrile rubber 220s, and 18 parts by weight of nitrile rubber 7030 into an internal mixer and plasticate for 90 seconds at a machine temperature of 90°C.

[0102] 2. Lift the heavy hammer and pour in 6 parts by weight of antistatic agent, 0.7 parts by weight of accelerator DM, 1.65 parts by weight of antioxidant OH3, 3.7 parts by weight of zinc carbonate, 0.4 parts by weight of stearic acid, 1.2 parts by weight of polyethylene glycol PEG-400, 1.6 parts by weight of wear-resistant oil and 1 / 3 of 13 parts by weight of ultrafine (gas phase method) white smoke, and plasticize for 60 seconds at a temperature of 110°C;

[0103] 3. Lift the heavy hammer to clean, then pour in one third of 13 parts by weight of ultrafine (gas phase) white smoke, plasticate for 60 seconds, temperature 115°C;

[0104] 4. Lift the heavy hammer to clean, pour in the remaining one third of 13 parts by weight of ultrafine (gas phase method) white smoke, and plasticize for 60 seconds at a temperature of 125°C;

[0105] 5. Lift the heavy hammer to clean, put down the heavy hammer to plasticize, repeat three times, time 120 seconds, temperature 135℃;

[0106] 6. Pour the plasticized rubber into the turbine and continue plasticizing for 180 seconds, roll it up, hang it on a rack to dry, let it cool, then weigh it, pack it in a PE bag, and store it for 24 hours for use;

[0107] 7. Add 1.2 parts by weight of insoluble sulfur as a vulcanizing agent to the stored rubber in an open mill and mix evenly, then roll it up into sheets; dry it for 4 hours and cut it into pieces for later use;

[0108] 8. The temperature of the rubber vulcanizing machine is 160℃, the pressure is 155KG / CM2, the exhaust is three times, and the vulcanization time is 320 seconds.

[0109] The finished product was tested and its performance parameters are shown in the following table:

[0110] Test results:

[0111] Oil resistance %: 4% expansion rate;

[0112] Heavy oil anti-slip: 0.47;

[0113] Antistatic Ω: 3.5;

[0114] Hardness A: 66;

[0115] Specific gravity g / cm 3 : 1.18;

[0116] Wear resistance mm 3 : 100;

[0117] Tensile strength MPa: 15;

[0118] Elongation %: 550;

[0119] Tear strength N / mm: 22;

[0120] Ozone level: 3.

[0121] Ozone test conditions (temperature: 40°C; humidity: 65% RH; ozone concentration: 50 pphm; time: 6 hours)

[0122] According to the final measured values ​​of the three embodiments: oil resistance: ≤6%, heavy oil anti-skid ≥0.46, antistatic performance ≤4Ω, the oil resistance and heavy oil anti-skid values ​​of the product obtained by this application have broken through the upper limit of the industry, and it has super adaptability in oily environments. Without being limited by any theory, the applicant believes that the nitrile rubber as the main rubber material in the above materials is the key factor to achieve oil resistance and heavy oil anti-skid, the antistatic agent is the key to achieve antistatic performance, and the specific ratio between the various materials will determine the final overall performance of the product.

[0123] Industrial Applicability

[0124] Since the rubber material obtained in this application has exceeded the upper limit of the industry in terms of oil resistance and heavy oil anti-slip properties, it has super strong adaptability in oily environments and is therefore expected to have broad industrial application prospects.

Claims

1. An oil-resistant, anti-slip and anti-static rubber material, comprising the following components: The weight ratio of nitrile rubber 220s to nitrile rubber 7030 is between 1.03-1.35, and the weight ratio of butadiene rubber to nitrile rubber 220s is between 0.28-0.

38.

2. The rubber material according to claim 1, wherein the weight ratio of the antistatic agent to the nitrile rubber 220s is 0.25-0.

33. The rubber material according to claim 1 , wherein the butadiene rubber is butadiene rubber BR1208.

4. The rubber material according to claim 1, which is composed of the following composition:

5. The rubber material according to claim 1, wherein the oil resistance of the rubber material reaches an expansion rate of less than 5%, heavy oil anti-slip ≥ 0.46, and antistatic effect is as low as less than 5 ohm resistance value.

6. A method for preparing the oil-resistant, anti-skid and anti-static rubber material according to any one of claims 1 to 5, the method comprising the following steps: 1) Put cis-1,4-butadiene rubber, nitrile rubber 220s and nitrile rubber 7030 into an internal mixer and plasticate for 90-100 seconds at a machine temperature of 90-100°C; 2) Then pour in small medicine and one third of ultrafine gas phase white smoke, and plasticate for 60-70 seconds at a temperature of 100-110°C, wherein the small medicine refers to other ingredients in the formula except butadiene rubber, nitrile rubber 220s, nitrile rubber 7030 and ultrafine gas phase white smoke; 3) Then pour in one third of ultra-fine gas phase white smoke, and plasticate for 60-70 seconds at a temperature of 110-115°C; 4) Pour in the remaining ultrafine gas phase white smoke and plasticate for 60-70 seconds at a temperature of 120-125°C; 5) Lift the hammer to clean, put down the hammer to plasticize, repeat at least three times, time 120-130 seconds, temperature 130-135℃; 6) Pour the plasticized rubber into the turbine, continue plasticizing for at least 180 seconds, and roll up to produce sheets; 7) Add insoluble sulfur as a vulcanizing agent to the stored rubber in an open mill, mix evenly, and roll up to produce sheets; 8) The temperature of the rubber vulcanizer is 160±10℃ and the pressure is 155±5KG / CM2 for vulcanization.

7. The method according to claim 6, wherein the vulcanization time is 320 seconds.

8. The rubber material according to any one of claims 1 to 5 and the rubber material prepared by the method according to any one of claims 6 to 7 are used for making shoe soles.

Citation Information

Patent Citations

  • Oil-resistant non-skid sole material and preparation method thereof

    CN103159993A

  • Light oil-proof sole material and preparation method thereof

    CN105733162A